The The Physicochemical and Antiplasmodial Properties of Microencapsulated Leaf Extract of Carica Papaya (Family: Caricaceae) - OYENIYI, Yinka James; Machi, Irene (AlQalam Journal of Medical and Applied Sciences, 2026)
Malaria remains a major global health challenge, and there is growing interest in plant-derived antimalarial agents as alternative or adjunct therapies. Carica papaya has shown notable antiplasmodial activity; however, its therapeutic potential is limited by poor stability, variable bioavailability, and rapid release when used in crude form. Microencapsulation using biopolymer-based systems offers a promising strategy to improve the stability and controlled delivery of phytochemicals. This study aimed to develop and evaluate sodium alginate-based microencapsulated formulations of Carica papaya leaf extract to improve encapsulation efficiency, enable controlled release, and enhance in vivo antiplasmodial activity. Microcapsules were prepared via ionotropic gelation using different sodium alginate concentrations to create various formulations (IM1, IM2, and IM3). The formulations were evaluated for encapsulation efficiency, morphology, swelling behavior, and in vitro drug release kinetics. The best-performing formulation (IM₃) was further tested for in vivo antiplasmodial activity using a Plasmodium berghei-infected Swiss albino mouse model. Parasitemia reduction was measured and compared with the crude extract, the negative control, and a standard antimalarial drug, and statistical analysis was conducted using appropriate significance tests (p < 0.001). The findings showed that polymer concentration significantly affected microcapsule properties, with IM3 demonstrating the highest encapsulation efficiency, structural stability, and a sustained drug-release profile, while IM2 exhibited a more balanced release pattern. In vivo studies indicated that the methanolic extract of Carica papaya significantly reduced parasitemia, with microencapsulated formulations showing markedly improved effectiveness. The IM3 formulation produced the strongest antiplasmodial effect among the test groups and showed enhanced performance compared to the crude extract, with statistically significant differences (p < 0.001). Sodium alginate-based microencapsulation greatly improves the stability, controlled release, and antimalarial effectiveness of Carica papaya leaf extract. The IM3 formulation demonstrates strong potential as a sustained-release phytopharmaceutical for malaria treatment, underscoring the importance of advanced formulation strategies in enhancing plant-derived therapeutic agents.